Tính giá trị của biểu thức: M= 4.( a-b ).(b-c)-(c-a)^2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, a x 6 = 3 x 6 = 18
b, a + b = 4 + 2 = 6
c, b + a = 2 + 4 = 6
d, a - b = 8 - 5 = 3
e, m x n = 5 x 9 = 45
Ta có: a+b+c=0
\(\Leftrightarrow\left(a+b+c\right)^2=0\)
\(\Leftrightarrow a^2+b^2+c^2+2\left(ab+bc+ac\right)=0\)
\(\Leftrightarrow2\left(ab+bc+ac\right)=0-1=-1\)
hay \(ab+bc+ac=-\dfrac{1}{2}\)
\(\Leftrightarrow\left(ab+bc+ac\right)^2=\dfrac{1}{4}\)
\(\Leftrightarrow a^2b^2+b^2c^2+a^2c^2+2ab^2c+2abc^2+2a^2bc=\dfrac{1}{4}\)
\(\Leftrightarrow a^2b^2+b^2c^2+a^2c^2+2abc\left(b+c+a\right)=\dfrac{1}{4}\)
\(\Leftrightarrow a^2b^2+b^2c^2+a^2c^2=\dfrac{1}{4}\)
Ta có: \(M=a^4+b^4+c^4\)
\(\Leftrightarrow M=a^4+b^4+c^4+2a^2b^2+2a^2c^2+2b^2c^2-2a^2b^2-2a^2c^2-2b^2c^2\)
\(\Leftrightarrow M=\left(a^2+b^2+c^2\right)^2-2\left(a^2b^2+a^2c^2+b^2c^2\right)\)
\(\Leftrightarrow M=1^2-2\cdot\dfrac{1}{4}=1-\dfrac{1}{2}=\dfrac{1}{2}\)
Vậy: \(M=\dfrac{1}{2}\)
Ta có : \(a+b+c=0\)
\(\Rightarrow\left(a+b+c\right)^2=0\)
\(\Rightarrow a^2+b^2+c^2=-2\left(ab+bc+ac\right)=1\) ( * )
\(\Rightarrow ab+bc+ac=-\dfrac{1}{2}\)
Lại có : \(\left(a^2+b^2+c^2\right)^2=4\left(ab+bc+ca\right)^2\) ( suy ra từ * )
\(\Rightarrow a^4+b^4+c^4=2\left(-\dfrac{1}{2}\right)^2=\dfrac{1}{2}\)
Vậy ...
a=2009,b=2010,c=2011
M=4(2009-2010)(2010-2011)=(2009-2011)^2=4
Đặt \(\frac{a}{2009}=\frac{b}{2010}=\frac{c}{2011}=k\)
=>a=2009k;b=2010k;c=2011k
Xét \(4\left(a-b\right)\left(b-c\right)=4\left(2009k-2010k\right)\left(2010k-2011k\right)\)
\(=4\left(-k\right)\left(-k\right)=4k^2\left(1\right)\)
Xét \(\left(c-a\right)^2=\left(2011k-2009k\right)^2=\left(2k\right)^2=4k^2\left(2\right)\)
Từ (1) và (2)
=>4(a-b)(b-c)=(c-a)2=4k2
Hay M=4k2
\(a+b+c=0\Leftrightarrow\left(a+b+c\right)^2=0\Leftrightarrow a^2+b^2+c^2+2\left(ab+bc+ac\right)=0\)
\(\Leftrightarrow14+2\left(ab+bc+ac\right)=0\Leftrightarrow ab+bc+ac=-7\)
Suy ra : \(\left(ab+bc+ac\right)^2=49\Leftrightarrow a^2b^2+b^2c^2+a^2c^2+2abc\left(a+b+c\right)=49\)
\(\Leftrightarrow a^2b^2+b^2c^2+a^2c^2=49\)
\(a^2+b^2+c^2=14\Leftrightarrow\left(a^2+b^2+c^2\right)^2=196\Leftrightarrow a^4+b^4+c^4+2\left(a^2b^2+b^2c^2+a^2c^2\right)=196\)
\(\Leftrightarrow a^4+b^4+c^4+2.49=256\) \(\Leftrightarrow a^4+b^4+c^4=98\)
Vậy ...
\(a+b+c=0\)
\(\Rightarrow\left(a+b+c\right)^2=0\)
\(\Leftrightarrow a^2+b^2+c^2+2ab+2bc +2ca=0\)
\(\Leftrightarrow2ab+2bc+2ca=-14\)
\(\Leftrightarrow ab+bc+ca=-7\)
\(\Rightarrow\left(ab+bc+ca\right)^2=49\)
\(\Leftrightarrow a^2b^2+b^2c^2+c^2a^2+2ab^2c+2abc^2+2a^2bc=49\)
\(\Leftrightarrow a^2b^2+b^2c^2+c^2a^2+2abc\left(a+b+c\right)=49\)
\(\Leftrightarrow a^2b^2+b^2c^2+c^2a^2=49\).
\(a^2+b^2+c^2=14\)
\(\Rightarrow\left(a^2+b^2+c^2\right)^2=14^2=196\)
\(\Leftrightarrow a^4+b^4+c^4+2\left(a^2b^2+b^2c^2+c^2a^2\right)=196\)
\(\Leftrightarrow a^4+b^4+c^4+2.49=196\)
\(\Leftrightarrow a^4+b^4+c^4=98\)